Environmental Pollution Liability Insurance of Health Risk and Corporate Environmental Performance: Evidence From China - Wu, Wenqing; Zhang, Pianpian; Zhu, Dongyang; Jiang, Xin; Jakovljevic, Mihajlo (Frontiers in Public Health, 2022)
Environmental pollution liability insurance (EPLI) is a type of insurance purchased by an enterprise to compensate the loss of the victims in the event of an environmental pollution incident. Although EPLI can realize the post-treatment of environmental pollution to a certain extent, there is still less understanding of whether EPLI can improve the environmental performance of enterprises. Taking A-share listed companies in heavily polluting industries as the research object, the treatment group samples were determined according to the Insurance coverage list announced by the Ministry of Environmental Protection in 2014 and 2015, and the empirical test model was further constructed. In order to ensure that there is no sample selection bias, the PSM method is used to preprocess the samples in this study, so as to ensure the robustness of the conclusions. The results of empirical tests show EPLI can significantly improve corporate environmental performance. Further analysis showed that higher public visibility is conducive to the positive environmental effects of EPLI. Compared with state-owned enterprises, non-state-owned enterprises have more significant implementation effects after the introduction of EPLI. On further examination, the result indicates that environmental pollution liability insurance can improve environmental performance by alleviating corporate financing constraints. The findings of this paper enrich the theory of the economic impact of environmental pollution liability insurance, which has a meaningful theoretical guidance for enterprises and policy makers.